Intestinal Barrier Dysfunction Exacerbates Neuroinflammation via the TLR4 Pathway in Mice With Heart Failure - Huo, Jun-Yu; Jiang, Wan-Ying; Yin, Ting; Xu, Hai; Lyu, Yi-Ting; Chen, Yuan-Yuan; Chen, Meng; Geng, Jie; Jiang, Zhi-Xin; Shan, Qi-Jun (Frontiers in Physiology, 2021)
Aims: The present study aimed to investigate alterations in neuroinflammation after heart failure (HF) and explore the potential mechanisms. Methods: Male wild-type (WT) and Toll-like receptor 4 (TLR4)-knockout (KO) mice were subjected to sham operation or ligation of the left anterior descending coronary artery to induce HF. Eight weeks later, cardiac functions were analyzed by echocardiography, and intestinal barrier functions were examined by measuring tight junction protein expression, intestinal permeability and plasma metabolite levels. Alterations in neuroinflammation in the brain were examined by measuring microglial activation, inflammatory cytokine levels and the proinflammatory signaling pathway. The intestinal barrier protector intestinal alkaline phosphatase (IAP) and intestinal homeostasis inhibitor L-phenylalanine (L-Phe) were used to examine the relationship between intestinal barrier dysfunction and neuroinflammation in mice with HF. Results: Eight weeks later, WT mice with HF displayed obvious increases in intestinal permeability and plasma lipopolysaccharide (LPS) levels, which were accompanied by elevated expression of TLR4 in the brain and enhanced neuroinflammation. Treatment with the intestinal barrier protector IAP significantly attenuated neuroinflammation after HF while effectively increasing plasma LPS levels. TLR4-KO mice showed significant improvements in HF-induced neuroinflammation, which was not markedly affected by intestinal barrier inhibitors or protectors. Conclusion: HF could induce intestinal barrier dysfunction and increase gut-to-blood translocation of LPS, which could further promote neuroinflammation through the TLR4 pathway.